Teacher competencies in job advertisements for teachers - Ville Mankki; Mirva Heikkilä; Lauri Kemppinen; Riitta-Leena Metsäpelto (Nordic Journal of Comparative and International Education)
Teaching requires a diverse range of competencies. This study investigates teacher competencies articulated in job advertisements for teaching positions in Finland. Given the global teacher recruitment challenges, particularly in rural schools, and the regional differentiation within Finland, the study also examines the variations across rural, semi-urban, and urban municipalities. Data were collected from a centralized recruitment website, resulting in 596 job advertisements for class teacher positions. A deductive qualitative content analysis was performed using the individual teacher competencies defined in the multidimensional adapted process model of teaching (Metsäpelto et al., 2022) as a framework. The findings highlight the prevalence of teacher competencies related to knowledge base of teaching and learning, social skills, and personal orientations. Notably, advertisements from rural municipalities featured fewer competencies compared to those from semi-urban and urban municipalities. By illustrating the desired teacher competencies in the field, this study provides a valuable tool for evaluating and developing teacher education goals and teacher recruitment strategies.